The Effect of Radioactive Iodine-129 in The Tap Water on The Development of The Thyroideal Nodular Formation in ElaziĞ and Bingol Areas - Aygen, Erhan; Doğru, Mahmut (Fırat University, 2003)
Aim: This prospective study was designed to the determine and discriminate the effect of radioactive 129I in the tap water on the development of the thyroideal nodular formation in Elazığ and Bingöl areas. Material and method: Sixty-two patients were taken into this study who were admitted to operations for nodular goitre, between March 2000 and June 2002. These patients divided into two groups, who live in Elazig referred as Group I (n=30), the other who live in Bingöl referred as Group II (n=32). β-radioactivities of the 129I were analysed taken specimens from tap water and nodules and normal tissue of the thyroid taken from the patients using tube supported plastic scintilator and SR8 scaler/ratemeter which are sensitive for β-radiation. Results: The mean radioactivity of the tap water of the patients take, normal thyroideal tissue and nodules were obtained to be lower in Group I than in Group II. Only tap water radioactivities were statistically significant between groups (p

Amaç: Elazığ ve Bingöl'de herkesin ortak kullanımı olan suda bulunan 129I'un nodüler guatr etyolojisindeki rolünü ve iki il arasındaki farklı durumu araştırmak üzere prospektif bir çalışma düzenlendi. Gereç ve yöntem: Mart-2000 ile Haziran-2002 tarihleri arasında nodüler guatr nedeniyle opere edilmek üzere yatırılan 62 hasta çalışmaya alındı. Bu hastalardan Elazığ'da yaşayanlar Grup I (n=30) ve Bingölde yaşayanlar ise Grup II (n=32) olacak şekilde iki gruba ayrıldı. Bu hastaların içme sularından, operasyon spesmenlerindeki nodül ve normal dokularından örnekler alınarak, β radyasyonuna hassas fotoçoğaltıcı tüp destekli plastik sintilatör ve SR8 scaler/ratemeter cihazından oluşan algılama sistemi ile 129I'un β radyoaktivitesi sayıldı. Bulgular: Grup I'deki hastaların içme suları, normal ve nodüler dokularındaki ortalama radyoaktivite seviyeleri, Grup II'deki hastalardan düşük olup sadece içme sularındaki seviyeleri arasında anlamlı farklılık vardı. Hem Grup I'de hem de Grup II'de nodüler dokuların, normal dokuya göre radyoaktivitesi daha fazla olup bu fark anlamlıydı (p
Elazığ ve Bingöl Yörelerinde İçme Suyundaki İyot-129'un Tiroid Dokusunda Nodüler Formasyona Etkisi